Konsep Moneter Al-Ghazali: Sejarah dan Fungsi Uang - Meiki Muttaqien; Udin Saripudin; Deden Gandana Madjakusumah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose- The purpose of this article is to provide an explanation and reasoning on the monetary concept written by Al-Ghazali in his book Ihya ‘Ulum al-Din. Methods- The literature review method is carried out to obtain relevant information regarding al-Ghazali's monetary concept. Finding - According to Al-Ghazali, money only functions as an intermediary to other goods and as a medium of exchange of goods. Money is not a commodity and therefore cannot be traded at a certain price. The money will make a good contribution if a country can make money as it functions. God created gold and silver to make it easy for humans to make fair transactions. The function of money according to al-Ghazali is appropriate to be a basic guide or guideline in Islamic economics. Implications- This article can provide benefits both theoretically and in practice regarding the concept of money in central civilization and its suitability with the present.